2009
DOI: 10.2341/08-016-l
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine-containing Acid Conditioner Preserves the Longevity of Resin-dentin Bonds

Abstract: SUMMARYThe current study evaluated the effect of 2% chlorhexidine digluconate (CHX) on the immediate and six-month resin-dentin bond strength (BS) and nanoleakage pattern (NL) of etch-andrinse adhesives when applied in aqueous or associated to the phosphoric acid conditioner. The occlusal enamel of 42 caries-free extracted molars was removed in order to expose a flat dentin surface. In groups 1 and 2 (control-C), the surfaces were acid etched with conventional phosphoric acid, and the adhesives Prime&Bond NT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 38 publications
2
85
0
6
Order By: Relevance
“…7,8,12,13,16 The chlorhexidine application showed no interference on immediate bond strength but resulted in higher bond strength values than the control group after 6 months, even when the chlorhexidine application time was reduced to 30 seconds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,12,13,16 The chlorhexidine application showed no interference on immediate bond strength but resulted in higher bond strength values than the control group after 6 months, even when the chlorhexidine application time was reduced to 30 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] In a few studies, researchers attempted to reduce this time to save both the professional's and the patient's time. 10,[12][13][14] However, none of these studies evaluated the reduced time of chlorhexidine application on the dentin of deciduous teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (13,24) have shown that caries-affected dentin applying the 2% CHX after acid etching, in order to minimize the degradation of resin-dentin bonds, does not negatively influence the immediate bond strength to sound permanent dentin. Similar results were observed in the present study in primary teeth, corroborating the findings of Ricci et al (17).…”
Section: Discussionmentioning
confidence: 99%
“…100 Besides, the degradation of the adhesive interface in primary teeth may be counteracted or blocked by the application of CHX as a therapeutic primer. 92,101 Avoiding to add another step in the adhesive treatment of dentin, 6,88 some investigators have studied the beneficial effects of incorporation CHX into the etchant 83,84 or the adhesive. 87,97,102,103,104 First strategy was alleged to reduce the effectiveness of CHX in the inhibition of MMPs and CCs, due to the limited contact time and the little concentration of CHX at the moment of adhesive application.…”
Section: Enzymatic Inhibitorsmentioning
confidence: 99%
“…76 CHX was accordingly shown to partially conserve the integrity of the hybrid layer, 77 , favoring bond durability. CHX can be used as an antiproteolytic "primer" solution directly applied on the dentin surface, or after phosphoric acid etching and rinsing 74,78,79,80,81,82 or incorporated into the acid etching agent 83,84 or within the adhesive system composition. 74,85,86,87 The use of 2% CHX solution as an effective and nonspecific protease inhibitor primer, after acid-etching, is attractive from a clinical point of view, since it is already used in other oral health situations as an antimicrobial agent.…”
Section: Enzymatic Inhibitorsmentioning
confidence: 99%